Community Empowerment at Sukagumiwang Village Elementary School, Sukagumiwang District, Indramayu Regency Using the Mind Mapping Method - Didik Himmawan; Ibnu Rusydi; Dini Syifa Agustina (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
In the world of education, learning methods are very necessary to facilitate the implementation of learning in the form of specific implementation of concrete steps so that an effective learning process occurs to achieve a certain goal, such as positive changes to students. Apart from learning methods, learning media also have an important role in increasing elementary school students' interest in learning, especially in lower classes, because students in lower classes are not yet able to think abstractly, so the material taught by teachers needs to be visualized in a more real or concrete form. One of the student contributions in reducing boredom and increasing students' understanding when learning is the program "PAI Learning Using the Mind Mappin Method in Elementary Schools." The aim of implementing this program is that students understand what has been conveyed by the teacher using this method, and it is hoped that students will be active. in classroom learning.